Aerodynamic influence of an alpine skier`s arms - Giljarhus, K. E. T.; Reid, R.; Liland, F. F. (Sports Engineering, 2022)
Understanding how postural changes in alpine skiing affect the overall aerodynamic drag is highly important for enhancing performance. Although the arm configuration of the athlete can have a significant impact on the overall drag force, this effect is currently less understood. The purpose of this investigation was to examine how the arms of an alpine skier influence the overall drag. Experiments were performed in a wind tunnel for a male and female athlete, and computational fluid dynamics simulations were performed on 3D scans of the athletes. The influence of the arm configurations in three different scenarios are considered; low-tucked, high-tucked, and flight postures. Consistent trends are found for both athletes and between the experiments and simulations. In general, the arms were found to be highly influential of the overall drag, and hence also performance in alpine skiing. For the low-tucked posture, the maximum variation in total drag area depending upon the angle of the underarms is 2.8%, with the lowest drag found with a medium angle of 20° to 25°. For the high-tuck posture, the difference in drag area between a closed and open posture was found to be 17% to 21%. The flight postures showed the highest influence of arm configurations, with a maximum difference in drag area of 64% between the considered postures. These results contribute to the understanding of aerodynamics in alpine skiing, and could be implemented directly in the training of athletes to improve their aerodynamic performance.